Goemai. (30th March 2015) - Tabain, Marija; Hellwig, Birgit
Abstract : Goemai is an Afroasiatic (Chadic, West Chadic A, Angas-Goemai group) language spoken in Central Nigeria. The name Goemai [ɡ m i ] is used by the speakers themselves to refer to both their language and their ethnic group. To outsiders, they are better known under the name Ankwe – a name that is also commonly found in the older linguistic, anthropological and historical literature. The Goemai live as farmers, fishermen and hunters in villages throughout the lowland savannah region south of the Jos Plateau and north of the Benue River, an area that is known geographically as the Great Muri Plains. The economy is based on agriculture (yam, millet, guineacorn, groundnut, beniseed) and is supplemented with fishing and hunting. Politically, the area belongs to Plateau State, and more specifically to the Local Government Areas Shendam and Qua'an Pan. Smaller Goemai-speaking communities are found in surrounding Local Government Areas as well as in Jos, the capital of Plateau State.